Spine surgery - Vaccaro, Alexander R; Baron, Eli M (Operative techniques, 2012)
Spine Surgery, 2nd Edition delivers step-by-step, multimedia guidance to help you master the must-know techniques in this field. Part of the popular and practical Operative Techniques series, this orthopaedics reference focuses on individual procedures, each presented in a highly visual, easy-to-follow format for quick reference.